AVALIAÇÃO DA QUALIDADE DE VIDA RELACIONADA À SAÚDE DE CRIANÇAS NASCIDAS PREMATURAS HOSPITALIZADAS EM UNIDADE DE TERAPIA INTENSIVA NEONATAL - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Epidemiological, observational, cross-sectional and quantitative research, which population consisted of a convenience sample of children with age between one and five years old born preterm (PT/n 17) who had been hospitalized in NICU and a control group (T/n 24), consisted by children born at term who did not need NICU care at birth. Data was processed in Excel 2010 and statistical analysis obtained through Statistical Package for Social Science (SPSS) version 15.0, p≤0,05 values were considered significant. Mean age of PT group was 32,52 months at time of data collection and 31,7 weeks of gestational age at birth, in T group mean age was 29,6 months and 39 weeks of gestational age. Length of stay in NICU was 41,17 days. Comparing TAPQOL scores between groups, only Anxiety and Motor functioning presented significant differences with PT group showing higher mean scores (both p=0,01 values). Among children born preterm, mean score for Stomach scale was higher in the group born below 32 weeks compared to group born between 32 and 36 weeks (p=0,05). For the total of children born preterm, there were significantly higher scores to: being male (Stomach), father´s school degree >11 years (Skin, Lungs, Sleep and Behavior), to have follow up with health professional (Skin), age of child ≥3 years (Lungs and Social Interaction) and social economic status A or B (Anxiety). Based on TAPQOL application it was possible to verify that children born preterm that had been hospitalized at HURCG NICU do not experience low quality of life. Some health and sociodemographic variables were associated to better HRQOL scores in children born preterm
Keywords: Prematuro; qualidade de vida; inquéritos e questionários; Premature; quality of life; surveys and questionnaires; CNPQ::CIENCIAS DA SAUDE